THE ROLE OF SCHOOL PRINCIPAL LEADERSHIP IN TEACHER MOTIVATIONTHE WORK OF HONORARY TEACHERS AT VOCATIONAL HIGH SCHOOLKARTIKA XX-I MAKASSAR - Rizal Afriantu; Burhanuddin; Uhud Darmawan Natsir; Chalid Imran Musa; Romansyah Sahabuddin (NETIZEN: JOURNAL OF SOCIETY AND BUSSINESS, 2025)
ObjectiveThis research aims to determine the role of the principal's leadership towards the work motivation of honorary teachers at SMK KARTIKA XX-I Makassar. This research uses a qualitative research method.The informants in the research the principal and 2 honorary teachers at SMK KARTIKA XX-I.Technique data collection methods used include interviews, observations, and documentation.The data analysis technique used is descriptive analysis qualitative.The research results show that the role of the principal's leadership the school fulfills its role as an educator, manager, supervisor, and motivator who helps increase the work motivation of honorary teachers, both through internal and external motivation approaches.This research highlights the importance of implementing adaptive and comprehensive leadership strategies to encouraging the spirit and performance of honorary teachers in the educational environment.